(untitled) (Journal of Forensic Medicine & Toxicology, 2012)
A 15 years old male was assaulted by a few people near his home. He suffered with a few abrasions, a contusion and minor fracture of skull bone. He survived for approximately 22 hrs while on conservative treatment. On post mortem examination, frothy blood was seen coming out from the right ventricle, along with plenty of air bubbles in jugular veins and in heart as well eliciting the diagnosis of air embolism. The case is being presented here for drawing attention towards the fact that simple head injury, augmented by lapses in treatment due to lack of suspicion, can lead to fatal degrees of air embolism.